زوائد معاني الأخبار للكلاباذي على الكتب الستة : دراسة تخريجية - مشعان، علي بخيت صالح حمد (Kuala Lumpur: Kulliyyah of Islamic Revealed and Human Sciences, IIUM Knowledge Sciences, International Islamic University Malaysia , IIUM, 2021)
This research deals with the study of the work of al-Imam Abu Bakr al-Kalabadhi (died 380 AH) titled Baḥr al-Fawaʾid, which was also known as Maʿani al-Akhbar, and its zawaʾid (addition) of extra hadiths to al-Kutub al-Sittah (the six canonical compendia of ḥadiths) in this particular book. al-Imam al-Kalabadhi included ḥadiths that he received via asanid (chains) that meet the asanid of the six compilers either at the level of their master-informants or those who were before them or the Companions or even another Companion whenever a ḥadith is reported through his channel. Thus, studying these extra ḥadiths will reveal the uniqueness of his collections compared to the six compendia. Some of the ḥadiths he reported can be traced back to a number of missing masanid (original collection of ḥadiths with chains). al-Imam al-Kalabadhi did not provide the status of the ḥadiths he mentioned in his book, rather he merely cited them with their chains of transmission. The researcher has examined all extra ḥadiths he found in the section which was selected for the research. Some of them are ṣaḥiḥ (sound), some are ḥasan (fair), some are ḍaʿif (weak), some are ḍaʿif jiddan (extremely weak), and some are mawḍuʿ (fabricated). The researcher has adopted the methodology of the muḥaddithun in this work and apply the method of ḥadīth criticism constructed by the prominent ḥadith scholars. All ḥadiths are supplied with the evaluation of its chain and the criticism is also supported with the opinions of early scholars on the authenticity of the ḥadiths.